Exogenous Growth: An Evidence From External Finance In Context Of Sri Lanka - Nisthar, S.; Vijayakumar, S.; Nufile, A.A.M.. (Faculty of Arts and Culture South Eastern University, Sri Lanka, 2022)
Inflow of external finance into Sri Lanka in terms of FDI is instrumental to overcome socio-economic issues detrimental to achieve economic growth. Objective of this study is to find nexus between Economic Growth and FDI in Sri Lanka by employing time series data from 1978 to 2020. The econometric techniques used in this study are listed as Kernel Fit, Confidence, Ellipse, Co integration, and Error Correction Mechanism – ECM. The dependent variable in the econometric model defined is GDP- GDP which is the proxy for Economic Growth in Sri Lanka. The independent variables are defined as FDI– FDI and EFI – EFI. There is a direct relationship or upward trend between GDP and Foreign Direct Investment. One percent increase in FDI – FDI leads to increase GDP – GDP by 1.39 percent. An increase of one percent in EFI – EFI lowers down GDP – GDP by 7.99 percent in long run. FDI and integration with the world market are the endogenous determinates which stimulate the economic growth of the county. As per the findings of this study, a positive relationship between Economic Growth and FDI as propounded by Endogenous Growth Model exists.
Keywords: Growth; External finance; Foreign direct investment and Unit root test